Turmeric Flour Supplementation Through Feed-in Biofloc System Cultivation on the Growth of Nilem Fish (Osteochilus hasselti) - Cahyono Purbomartono; Dhika Rahma Fauziyyah; Arief Husin (Sainteks, 2022)
Nilem fish (Osteochilus hasselti) is favored by the community because of its chewy meat texture, good taste, and relatively cheap price, so it has the potential to be developed. However, the growth of nilem fish is slow therefore it needs to be given an immunostimulant to increase its growth. Biofloc is known as a cultivation system that can maintain water quality and provide sufficient floc for additional fish feed. This study aims to determine the effect of using turmeric flour in feed to increase the growth of nilem fish reared in the biofloc system. The study used a completely randomized design (CRD), with 3 treatments and 1 control each repeated 4 times. The treatments were supplementation of turmeric flour through feed at a dose of 1.125 g (B), 0.75 g (C), and 0.375 g (D) kg-1 feed and control (A) in cultivation with a biofloc system. The study lasted for 90 days with feeding 3%/kg of biomass weight given 2 times a day, in the morning and evening. Parameters observed in this study were weight (WG) and length growth (LG), daily growth rate (SGR), feed conversion ratio (FCR) and feed efficiency (EF). The data collection method was carried out by weighing and measuring the weight and length of the fish and the amount of feed consumed. The data obtained were collected and analyzed using SPSS 2.0.The results showed that supplementation of turmeric flour through feed reared in the biofloc system could increase weight and length growth, daily growth rate, feed conversion ratio, and feed efficiency. The optimal dose was obtained in the treatment of 1.125 g kg-1 feed (B), proving that supplementation of turmeric flour through feed has the potential to be applied to fish culture using the biofloc system.